Evaluation of the Effectiveness of Rutan and Karsil in Correcting Antipyrine Pharmacokinetics Disorders in Rabbits with Acute Toxic Hepatitis During the Growth Period (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study investigates the pharmacokinetic features of antipyrine and the effectiveness of Rutan and Karsil in correcting its alterations in prepubertal rabbits with acute toxic hepatitis. It was established that carbon tetrachloride (CCl₄) administration in young rabbits led to significant disturbances in antipyrine pharmacokinetics, including a marked prolongation of the half-life, a decrease in metabolic clearance and elimination constant, along with an increase in the area under the pharmacokinetic curve (AUC). These changes persisted clearly during the first week after toxin exposure. Administration of Karsil and Rutan successfully reversed these pharmacokinetic impairments. Since antipyrine elimination occurs after hepatic metabolism, it is assumed that Rutan, like Karsil, counteracts the suppression of the monooxygenase system in hepatocytes. Considering the strong antioxidant activity of both agents, their positive effects on antipyrine pharmacokinetics are likely associated with the restoration of structural and functional integrity of the endoplasmic reticulum membranes, where the monooxygenase enzyme system is localized. The authors conclude that Rutan may be considered for use in pediatric clinical practice as a hepatoprotective agent that enhances the liver’s detoxification capacity, particularly in pathologies of the hepato-biliary system.